CIPP 평가 모형을 적용한 한의과대학 교육 프로그램 평가 지표 개발 - 이규영; 박해모; 선승호; Kyou Young Lee; Haemo Park; Seung Ho Sun (대한예방한의학회지, 2024)
Objective : In this study, we aimed to develop evaluation indicators for college of Korean medicine education programs using the CIPP (Context, Input, Process, Product) evaluation model. Method : A draft of evaluation indicators were developed through literature review, and a delphi survey was conducted to verify the evaluation indicators. The delphi survey was conducted in two rounds, and CVR (Content Validity Ratio), consensus, and convergence were analyzed to verify the validity of the delphi survey results, and CV (Coefficient of Variation) was analyzed to verify the stability of the delphi survey results. Results : We developed an evaluation indicators for college of Korean medicine education programs consisting of 4 evaluation areas, 35 evaluation items, 35 detailed evaluation Items evaluation scale, and 105 detailed evaluation items. Conclusion : This study is the first to develop evaluation indicators for college of Korean medicine education programs that has secured the reliability of experts by conducting a delphi survey. It is believed that it can contribute to the establishment and refinement of the educational program evaluation system for all college of Korean medicine.